2008
DOI: 10.1097/gme.0b013e31811ece0a
|View full text |Cite
|
Sign up to set email alerts
|

Women are periodontally healthier than men, but why don't they have more teeth than men?

Abstract: The apparent paradox of having fewer teeth despite better periodontal health in women compared with men is related to an increased bone turnover rate and socioeconomic conditions such as low education and low social status. Periodontal health is even worse if these factors are combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 27 publications
9
53
1
Order By: Relevance
“…A rapid decrease in the number of remaining teeth is observed in post-menopausal women, regardless of good oral care, compared with men. 12 As some studies have reported, dentition status may influence the MCW. 13,14 However, further adjustment for the number of teeth remaining did not change the odds ratios of having low spine BMD or spinal osteoporosis estimated using DXA among the MCW quartiles in our recent study.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid decrease in the number of remaining teeth is observed in post-menopausal women, regardless of good oral care, compared with men. 12 As some studies have reported, dentition status may influence the MCW. 13,14 However, further adjustment for the number of teeth remaining did not change the odds ratios of having low spine BMD or spinal osteoporosis estimated using DXA among the MCW quartiles in our recent study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the results give evidence of distinct responses between men and women in the metabolic pathways connecting obesity and tooth loss. Besides their impact on fat metabolism and fat distribution, protective effects of estrogens may be relevant to alveolar bone loss and tooth loss (Meisel et al, 2008). In patients with periodontitis and concomitant postmenopausal osteoporosis, a lack of this hormone may be deleterious (Lerner, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes toward and biology of oral health are very different between men and women, resulting in a dimorphism in susceptibility to periodontitis (Meisel et al, 2008;Shiau and Reynolds, 2010;Russell et al, 2013). Thus, the results give evidence of distinct responses between men and women in the metabolic pathways connecting obesity and tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal women who undergo estrogen replacement therapy had less tooth and oral bone loss than postmenopausal women who are not undergoing hormone estrogen replacement therapy. Meisel et al [3] randomly selected participants who were evaluated to test different hypotheses that could explain the paradox between periodontal health and number of teeth present among men and women. Diagnostic periodontal parameters, attachment loss, and number of teeth were determined.…”
Section: The Role Of Female Hormonesmentioning
confidence: 99%
“…In a comparison between men above 50 years of age, and postmenopausal women with and without HRT, it was found that only women who didn't take estrogen after menopause have fewer teeth than men. The use of hormonal therapy supplements reduced the urinary deoxypyridinoline excretion and the extent of attachment loss, thus associated with the increase in number of teeth [3].…”
Section: Introductionmentioning
confidence: 99%